A Model for Scaling Undergraduate Research Experiences: The Global Ethnohydrology Study. Issue 1 (March 2019) - Ruth, Alissa; Wutich, Amber; Brewis, Alexandra
Engaging students early as researchers is a potentially powerful tool for both encouraging a diversity of undergraduates to consider career-tracks in disaster/emergency management and building the skills essential to those fields. Traditional faculty-centered, lab-based research apprenticeship models are limited in their capacity to scale. Within large, diverse public institutions, there is accordingly a challenge of how to make such experiences readily available to a variety of students with diverse backgrounds and levels of preparation. To this end, we designed the Global Ethnohydrology Study, a scaled research training and mentorship program that integrates undergraduates in data collection (through fieldwork) and analysis (through lab research) in to a multi-sited, multi-year research program on the perception of water and climate issues cross-culturally. Here we explain the strategy, outcomes, and some keys to success to this approach of broadening access to research experiences, and suggest ways educators could adopt similar strategies in their instructional designs.